2020
DOI: 10.1101/2020.07.08.20148999
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Artificial Intelligence-Assisted Loop Mediated Isothermal Amplification (ai-LAMP) for Rapid and Reliable Detection of SARS-CoV-2

Abstract: Until vaccines and effective therapeutics become available, the practical way to transit safely out of the current lockdown may include the implementation of an effective testing, tracing and tracking system. However, this requires a reliable and clinically validated diagnostic platform for the sensitive and specific identification of SARS-CoV-2. Here, we report on the development of a de novo, high-resolution and comparative genomics guided reverse-transcribed loop-mediated isothermal amplification (L… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Tests targeting more than one gene had better sensitivity than tests targeting a single gene ( Supplementary Figure 4 ). Three studies showed a specificity >90% 41 , 47 , 51 and no covariate explained the heterogeneity. Preprint publication (13 studies) was not associated with significantly different results than peer-reviewed, published, studies (16 studies).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…Tests targeting more than one gene had better sensitivity than tests targeting a single gene ( Supplementary Figure 4 ). Three studies showed a specificity >90% 41 , 47 , 51 and no covariate explained the heterogeneity. Preprint publication (13 studies) was not associated with significantly different results than peer-reviewed, published, studies (16 studies).…”
Section: Resultsmentioning
confidence: 91%
“…Three studies showed a specificity >90% 41,47,51 and no covariate explained the heterogeneity. Preprint publication (13 studies) was not associated with significantly different results than peer-reviewed, published, studies (16 studies).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations